The affective turn in the history of human formation. A memory of schooling and emotions - Escolano Benito, Agustín (Historia y Memoria de la Educación, 2018)
This paper examines various aspects of the impact that the affective turn had in the history of education. More specifically, it focuses on the interpretation of the emotional underpinnings retained on the canvas of memory that are revealed in textual, written, oral and iconic representations of the subjects. We revise certain fields affecting the reconstruction of experiences relating to spaces, time frames, material devices and other contexts in which the empirical culture of the school is expressed. We then attempt an integration of these elements of the subjects’ sentimental education into the processes of the construction of identity narratives and even into the new therapeutical perspectives of patrimonial education.